Intermediate statistics a modern approach - Stevens, James P. (Lawrence Erlbaum Associates, 2007)
Written for those who use statistical techniques, this text focuses on a conceptual understanding of the material. It uses definitional formulas on small data sets to provide conceptual insight into what is being measured. It emphasizes the assumptions underlying each analysis, and shows how to test the critical assumptions using SPSS or SAS.